Assessment on Ecological Service Value of Important Reservoir-type Water Sources——Taking Zhushuqiao Reservoir for Example - PENG Xiulian; HUANG Hongjun; SHE Kai; XIE Lei; LI Donglin (Renmin Zhujiang)
This paper takes Zhushuqiao Reservoir, an important drinking water source in ChangshaCity as the research object, estimates and calculates that the total ecological service value ofZhushuqiao Reservoir is 4.449 billion yuan per area and 7.669 billion yuan per area respectivelyby the methods of value equivalent factor per unit area and intermediate substance conversionvalue, and proposes, measures to enhance the ecological service value of reservoir-type watersources by comparing different calculating results from the two methods, which can providereference for ecological compensation mechanism improvement, ecological protection and economicdevelopment, etc.